Increased rectal cell proliferation following alcohol abuse. Issue 3 (1st September 2001) - Simanowski, U A; Homann, N; Knühl, M; Arce, L; Waldherr, R; Conradt, C; Bosch, F X; Seitz, H K
Abstract : BACKGROUND: Epidemiological data indicate an increased risk for rectal cancer following chronic alcohol consumption. As chronic ethanol ingestion leads to rectal hyperregeneration in experimental animals, indicating a state of increased susceptibility to carcinogens, we studied cell proliferation in alcohol abusers. METHODS: Rectal biopsies were taken from 44 heavy drinkers and 26 controls. Cell proliferation, including proliferative compartment size, was measured by immunohistological staining for proliferative cell nuclear antigen (PCNA) and Ki67, and by in situ hybridisation for histone H3. Quantification of cell proliferation using PCNA staining was evaluated in 27 alcohol abusers and 12 controls. In addition, immunohistology was performed for cytokeratins and gene products of Rb1, bcl-2, and p53. RESULTS: Heavy drinking resulted in increased cell proliferation of the rectal mucosa, as shown by increased detection of different proliferation markers. However, cell differentiation regarding cytokeratin expression patterns was unchanged as well as regulatory factors involved in carcinogenesis and/or apoptosis. CONCLUSION: Chronic alcohol abuse leads to rectal mucosal hyperproliferation in humans, a condition associated with an increased cancer risk.